2019
DOI: 10.1007/s40820-018-0235-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Engineering Highly Efficient Porous Semiconductor Photocatalysts Derived from Metal–Organic Frameworks

Abstract: Highlights In this review, we survey the recent developments in the fabrication of metal–organic framework (MOF)-derived porous semiconductor photocatalysts toward four kinds of energy-/environment-related reactions.A comprehensive summary of highly efficient MOF-derived photocatalysts, particularly porous metal oxides and metal sulfides, and their heterostructures are provided.Enhanced photocatalytic performance achieved with MOF-derived porous heterostructures as the photocatalyst is discussed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
96
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(98 citation statements)
references
References 139 publications
0
96
0
2
Order By: Relevance
“…Emerging as a new category of crystalline porous materials with ultrahigh porosity and abundant metal active sites, metal-organic frameworks (MOFs) are assembled by the coordination bond between metal ions and organic ligands, giving the enormous application prospects [20][21][22]. Recently, extensive researches related to transition metal-based MOFs have been demonstrated that they are the appealing candidates for energy conversion and storage [23][24][25]. However, most MOFs electrodes unavoidably suffer from inherently low electrical conductivity and instability, which has greatly thwarted their capacitive performances and rate capacities [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging as a new category of crystalline porous materials with ultrahigh porosity and abundant metal active sites, metal-organic frameworks (MOFs) are assembled by the coordination bond between metal ions and organic ligands, giving the enormous application prospects [20][21][22]. Recently, extensive researches related to transition metal-based MOFs have been demonstrated that they are the appealing candidates for energy conversion and storage [23][24][25]. However, most MOFs electrodes unavoidably suffer from inherently low electrical conductivity and instability, which has greatly thwarted their capacitive performances and rate capacities [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis with semiconductor materials has attracted considerable interests due to the potential applications in solar fuel production, environmental clean‐up and water purification . During the past decades, several types of oxide‐based photocatalysts such as simple oxides (TiO 2 , ZnO and α‐Fe 2 O 3 , etc.…”
Section: Figurementioning
confidence: 99%
“…Photocatalysts preparation : The TiO 2 (B) nanosheet powders were prepared by following a modified synthetic method reported by Wang et al . Typically, 1 mL of TiCl 4 and 30 mL of ethylene glycol were mixed together followed by addition of 1 mL water.…”
Section: Figurementioning
confidence: 99%
“…Among the well-known approaches for the synthesis of nanomaterials, this MOF-templated approachc an endow the derived nanomaterials with high porosity,c rystallinity,a nd importantly,u niformity of the morphology and elemental distribution, which are the keys for efficient separation and transportation of the photoexcited chargec arriers. [19,20] The bandgapc ould also be finely optimizedb yf acilely changing the molarr atio of different parts of the parent MOFs to improve light-harvesting capability and charge-carrier separation efficiency. [21][22][23][24] Molybdenums ulfide (MoS 2 ), ap -types emiconductor,h as been studied as cocatalyst in semiconductor-based photocatalysts.…”
Section: Introductionmentioning
confidence: 99%